Mindfulness and its Contribution to the Performance of the Frontal Pronation Skill on the Horizontal Bar of Gymnastics for Students - Zaid Sami Yasir; Yassin Alowan Ismail (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study aimed to identify the level of mental alertness and the numerical values of the results of the performance of the frontal pronation skill on the mind apparatus of the gymnastics of the students, and to identify the percentage of the contribution of the mindfulness to the performance of the front pronation skill on the mind apparatus of the gymnastics of the students, the descriptive approach in the method of relational relations was adopted on a sample of (82) students deliberately chosen (89.13%) from their community represented by the third stage students in the Department of Physical Education and Sports Sciences at the College of Basic Education / Al-Mustansiriyah University who are continuing in the official working hours for the academic year (2020/2021), in addition, the specialized mental alertness scale was approved by students of faculties and departments of Physical Education and Sports Sciences, and a video recording to test students’ performance of the frontal pronation skill on the barbell device in your gymnastics, and the researchers applied these two tools to the sample and process its results with the (SPSS) system to be the extracts and applications in that the third stage students in the Department of Physical Education and Sports Sciences in the College of Basic Education need to improve the level of mental alertness and improve the level of their performance of the frontal pronation skill on their horizontal bar, mindfulness is positively related, contributes, and influences the improvement of their performance level for this skill, and it is necessary to intensify efforts between teachers of gymnastics and specialists in sports psychology and their cooperation in support of raising the level of mental alertness according to scientific, non-improvisational foundations because of its important role in improving the performance of the frontal pronation skill on horizontal bar device.